ByzRev 02.2020.026: Stefan Rebenich – Hans-Ulrich Wiemer (eds.), A Companion to Julian the Apostate: (Brill’s Companions to the Byzantine World 5). Leiden – Boston: Brill 2020. - Tougher, Shaun (The Byzantine Review, 2020)
Stefan Rebenich – Hans-Ulrich Wiemer (eds.), A Companion to Julian the Apostate (Brill’s Companions to the Byzantine World 5). Leiden – Boston: Brill 2020. xiv, 481 pp. – ISBN: 978-90-04-41456-3 (€ 188.00)